2022
DOI: 10.1186/s12859-022-04966-7
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning-based data mining in medical examination data: a biological features-based biological age prediction model

Abstract: Background Biological age (BA) has been recognized as a more accurate indicator of aging than chronological age (CA). However, the current limitations include: insufficient attention to the incompleteness of medical data for constructing BA; Lack of machine learning-based BA (ML-BA) on the Chinese population; Neglect of the influence of model overfitting degree on the stability of the association results. Methods and results Based on the medical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 80 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Also, there is a risk of overfitting with many biomarkers in the same model 79 . Recently Yang et al 80 suggested a composite ML-BA based on the stacking technique with a simple meta-model to avoid overfitting and improved the performance of the BA estimates in predicting different health outcomes 80 . A brief description of the stacking method is provided in the Supplementary information file.…”
Section: Ba Estimation Methodsmentioning
confidence: 99%
“…Also, there is a risk of overfitting with many biomarkers in the same model 79 . Recently Yang et al 80 suggested a composite ML-BA based on the stacking technique with a simple meta-model to avoid overfitting and improved the performance of the BA estimates in predicting different health outcomes 80 . A brief description of the stacking method is provided in the Supplementary information file.…”
Section: Ba Estimation Methodsmentioning
confidence: 99%